Desenvolvimento de iogurte à base de leite de cabra com extrato hidrossolúvel de soja - Silva, Danielle Cristina Guimarães da (2010)
This study was realized with the objective assess under the sensory aspects, chemical, physical, physical-chemical and microbiological yogurts made with goat milk and added soybean hydro soluble extract (SHSE). In the first stage, the yogurts were developed based on goat milk with 0%, 10%, 20% and 30% protein of SHSE adjusted to protein content of milk and subsequently evaluated using the Test Ordering Preference and Acceptance Test. The result of the first sensory study showed that the yoghurt base of goat milk most preferred were the control (without addition of SHSE) and with 20% protein of SHSE adjusted to protein content of milk. The sensory test acceptance identified the yogurt-based milk goat strawberry flavor more accepted were the control with 20% protein of SHSE adjusted to protein content of milk. It was concluded that the use of goat milk in the preparation of yoghurt was satisfactory and that the addition of 20% protein of SHSE adjusted to protein content of milk was sensory accepts. The second step consisted of adding of culture probiotic Bifidobacterium lactis during the development of treatments of yogurt more accepts sensory and evaluation aspects chemical, physical and physico-chemical and microbiological tests for 29 days at 4C. In relation to analysis of protein and fat, added treatments of SHSE showed higher levels. The highest values of viscosity and water holding capacity were obtained in the treatments in wich there were supplemental SHSE. The results for syneresis of yoghurt showed that the treatments added SHSE presented lower values. The analysis of folate in yogurt presented the results of 67 g/100 g for the yogurt to milk goats, 135 g/100 g for the yogurt added of SHSE, 180 g/100 g for the yogurt added to the culture probiotic Bifidobacterium lactis and 195g/100 g added to the treatment of SHSE and probiotic culture. The determination of the concentration of lyophilized cells of microorganisms (Streptococcus thermophillus and Lactobacillus delbrueckii subsp. bulgaricus and bacteria probiotic Bifidobacterium lactis) had counts of 1,3 x 108 and 3,6 x 108 respectively. The determination of viable cell count during storage of yoghurts showed that only treatment in which there was addition of SHSE, the number of lactic acid bacteria was found lower than expected. The enumeration of Bifidobacterium lactis showed that treatments of yogurts which there were inoculated with probiotic culture showed microbial viability during storage, showing variation of 1,6 x 108 a 3,1 x 107 for the treatment of yogurt without the addition of SHSE and variation of 1,1 x 108 to 2,7 x 107 for yoghurt with aqueous extract of soy. From these results, it appears that the yogurts showed viable under the chemical aspects, physical and physico-chemical parameters during storage time of 29 days. The addition of SHSE interfered negatively in the count of viable cells and bifidobacteria.